2021
DOI: 10.1038/s41467-021-24996-8
|View full text |Cite
|
Sign up to set email alerts
|

Photopatterned microswimmers with programmable motion without external stimuli

Abstract: We introduce highly programmable microscale swimmers driven by the Marangoni effect (Marangoni microswimmers) that can self-propel on the surface of water. Previous studies on Marangoni swimmers have shown the advantage of self-propulsion without external energy source or mechanical systems, by taking advantage of direct conversion from power source materials to mechanical energy. However, current developments on Marangoni microswimmers have limitations in their fabrication, thereby hindering their programmabi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
24
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 35 publications
(24 citation statements)
references
References 34 publications
0
24
0
Order By: Relevance
“…The indices in the containers were translated to QR‐coded microparticles fabricated through an optofluidic maskless lithography (OFML) system (Figure 1c). [ 31 ] With a digital mirror device (DMD) to alter the pattern of UV light on a photocurable resin without a photomask, on‐demand and high‐throughput fabrication of QR‐coded microparticles is possible. Owing to the transparency of the thin QR‐coded microparticles and container lids, the QR code can only be observed with a low depth of focus (Figure 1d).…”
Section: Resultsmentioning
confidence: 99%
“…The indices in the containers were translated to QR‐coded microparticles fabricated through an optofluidic maskless lithography (OFML) system (Figure 1c). [ 31 ] With a digital mirror device (DMD) to alter the pattern of UV light on a photocurable resin without a photomask, on‐demand and high‐throughput fabrication of QR‐coded microparticles is possible. Owing to the transparency of the thin QR‐coded microparticles and container lids, the QR code can only be observed with a low depth of focus (Figure 1d).…”
Section: Resultsmentioning
confidence: 99%
“…The motion of the Marangoni-propulsion micro-robots could change by changing their shape. [20] In previous research, the motion control of the micro-robots has been reported by changing their morphology responding to the stimuli through the volume change of the stimuli-responsive hydrogel. [9,43] Thus, in the future, we believe that the autonomous untethered micro-robots with not only the detecting the environmental information but also the motion control is realized through the volume change of the stimuli-responsive hydrogel.…”
Section: Discussionmentioning
confidence: 99%
“…[17] In addition, previous Marangoni-propulsion micro-robots achieved environmental remediation application, [18] light-driven micro-robots, [19] and programmable motion by photo-patterning of hydrogel. [20] For practical use of Marangoni-propulsion micro-robots, it is required to have the intelligence to detect the external environment for acting autonomously. [21] However, previous works have been mainly focused on the motility of the Marangoni micro-robots and thus the Marangoni-propulsion micro-robots integrated with wireless micro-scale sensors that can sense the external environment and transmit the obtained information have not been achieved.…”
Section: Introductionmentioning
confidence: 99%
“…There are a number of recent reports that highlight the importance of reinventing underappreciated actuation mechanisms. A report utilized the Magangoni effect to generate programmable actuators without external stimuli [ 173 ] ( Figure 14 a,b). With this, the authors developed a water surface Marangoni microswimmer with high programmability.…”
Section: Inorganic Additivesmentioning
confidence: 99%
“… ( a , b ) Schematic and demonstration of programmable Marangoni microswimmers made of PVA-embedded hydrogel. Embedded PVA is used as fuel, which reduces the local surface tension, leading to propulsion without external stimuli; adapted with permission from [ 173 ]. Copyright 2021 NPG.…”
Section: Figurementioning
confidence: 99%